Analisa Teknis Pengaruh Pemindahan Ruang Penumpang Dari Depan ke Bagian Belakang Terhadap Stabilitas Kapal Crew Boat Aluminium - JAILANI, ABDUL KADIR JAILANI (Techno Bahari, 2022)
Operation of crewboats in areas suffering from petroleum to be free from accidents. Therefore, the ease of operation of the ship is the main thing. The position of the ferry room and control room behind the PSV ship with the VS 493 series and the crewboat produced by Chantiers Allais is considered to be able to increase the comfort of the passenger room and the control room with only one maneuver position can facilitate the operation of the ship. The crewboat ship KCT 1902 is a ship already operating in an oil drilling area with a ferry space in front and a cargo deck at the rear. To be able to participate in the tender again, this ship must have a passenger room in the back and a cargo deck in front. The purpose of this thesis is to analyze the transfer of passenger space from the technical side and from the economic side. From the results of technical analysis, there was an increase in weight of 0.56 tons and a significant shift in point. This result led to changes to the ship, but the changes to be faced still have to be made. From the results of the economic analysis, it was found that the capital needed was Rp. 26,669,803,218.01, operating costs per year was Rp. 3,624,750.00 and income per year was Rp. 11,343,105,000.00, a Break Event Point was obtained in the 7th year.